Effects of sodium-glucose cotransporter-2 inhibitors and dipeptidyl peptidase-4 inhibitors on diabetic retinopathy and its progression: A real-world Korean study - Chung, Yoo-Ri; Ha, Kyoung Hwa; Lee, Kihwang; Kim, Dae Jung (PloS one, 2019)
The sodium-glucose cotransporter-2 inhibitors (SGLT2is) reduce the incidence of macrovascular complications of diabetes, while their effect on diabetic retinopathy has not been clarified. We compared the effects of SGLT2is with those of dipeptidyl peptidase-4 inhibitors (DPP4is) on the risk of diabetic retinopathy and its progression in people with type 2 diabetes. We performed a retrospective cohort study among people with type 2 diabetes who started on a SGLT2i or DPP4i from 2014 to 2016 according to the Korean National Health Insurance Service database. Subjects initiated on a SGLT2i or DPP4i were matched on a 1:1 basis according to their propensity scores, and Cox proportional hazards regression models were used to calculate the hazard ratios for the risk of diabetic retinopathy and its progression. After propensity score-matching, 41,430 patients without a history of diabetic retinopathy were identified as new users of a SGLT2i (n = 20,175) or DPP4i (n = 20,175). The hazard ratio (95% CI) for diabetic retinopathy was 0.89 (0.83-0.97) for SGLT2i initiators compared with DPP4i initiators. In patients with a history of diabetic retinopathy (n = 4,663 pairs), there was no significant difference in diabetic retinopathy progression between SGLT2i initiators and DPP4i initiators (hazard ratio 0.94, 95% CI 0.78-1.13). This real-world cohort study showed that SGLT2is might be associated with lower risk of diabetic retinopathy compared with DPP4is. Randomized controlled trials are needed to investigate the long-term effect of SGLT2is in diabetic retinopathy in people with diabetes.